Evaluation and Improvement of Pumping Well Operating Conditions in an Oil Field Block Based on Grey Correlation Analysis - Zi-Ming Feng* (Faculty of Mechanical Engineering in Slavonski Brod, Faculty of Electrical Engineering in Osijek, Faculty of Civil Engineering in Osijek, 2021)
The "Oil and Gas Water Well Production Data Management System Database" provides great assistance for oilfield production, monitoring, and management. However, due to the harsh conditions of oil field wells and the lack of some test data, traditional management methods are no longer suitable for present condition. At the same time, optimization analysis for a single oil well has a high cost and low efficiency, and it is difficult to achieve the modern management goal of large-scale pumping well groups. In this paper, the grey correlation method is used to analyze the direct correlation between the influencing factors and the system efficiency, surface equipment driving efficiency, and wellbore lifting efficiency, and the improvement method against factors with strong correlation is prioritized. A multi-node evaluation index system for pumping well systems and corresponding improvement methods were constructed, and evaluation software was compiled. This technology considers the running condition of the pumping unit in one oil field block, and selects the oil wells to be improved according to the evaluation index, and puts forward the targeted improvement methods according to the common problems of the oil well. This paper provides a set of reliable technical methods for the efficient management of the oil well in the oil field block.